Program Kemitraan Masyarakat di Sekolah Dasar Inpres Winangun Untuk Pelatihan Pemanfaatan Aplikasi Kecerdasan Buatan Dalam Mengembangkan Konten Pembelajaran: Community Partnership Program at SD Inpres Winangun for Training on the Use of Artificial Intelligence Applications in Learning Content Development (Tumou Tou: Jurnal Pengabdian Masyarakat, 2024)
Sekolah Dasar Inpres Winangun Manado is an elementary school located in the Malalayang District of Manado City. As AI democratization spreads widely to educational institutions,  it become a challenge for schools to adapt. To address this challenge, in collaboration with the school, we conducted a training to support teachers at the school with new knowledge, insights, and practical understanding to develop and deliver learning content effectively using Artificial Intelligence Applications. The implementation method in this program includes initial preparation with partners, needs assessment, training material preparation, and the execution of training, which covers basic concepts and the introduction of artificial intelligence applications, simulation of application usage, and practical guidance. This process concludes with evaluation and report preparation to assess the program's success and document the results. Evaluation findings indicate that most teachers find artificial intelligence beneficial in enhancing teaching quality, although many also express the need for further training to maximize AI application. This suggests the positive potential of AI in education, but continuous support is needed to enhance teachers with technical skills.